2020
DOI: 10.3389/fcimb.2020.00272
|View full text |Cite
|
Sign up to set email alerts
|

A Human 2D Primary Organoid-Derived Epithelial Monolayer Model to Study Host-Pathogen Interaction in the Small Intestine

Abstract: Gut organoids are stem cell derived 3D models of the intestinal epithelium that are useful for studying interactions between enteric pathogens and their host. While the organoid model has been used for both bacterial and viral infections, this is a closed system with the luminal side being inaccessible without microinjection or disruption of the organoid polarization. In order to overcome this and simplify their applicability for transepithelial studies, permeable membrane based monolayer approaches are needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 62 publications
3
88
1
Order By: Relevance
“…These round structures are difficult to infect with viruses: receptors needed for infection are mostly located inside the organoid. As with HAE cultures, round gut organoids can be transformed to an open organoid model where cells grow on a Transwell ® , so that they can be reached from the upper and lower sides to establish infections [ 6 , 26 , 42 , 43 ]. This model system is ideal for infectious-disease studies and to test antimicrobial drugs.…”
Section: Technical Challengesmentioning
confidence: 99%
“…These round structures are difficult to infect with viruses: receptors needed for infection are mostly located inside the organoid. As with HAE cultures, round gut organoids can be transformed to an open organoid model where cells grow on a Transwell ® , so that they can be reached from the upper and lower sides to establish infections [ 6 , 26 , 42 , 43 ]. This model system is ideal for infectious-disease studies and to test antimicrobial drugs.…”
Section: Technical Challengesmentioning
confidence: 99%
“…Previous reports indicated that L. monocytogenes preferably traverses the intestinal epithelium both through goblet cells and M cells at the Peyer's patch level [ 71 , 72 ]. Recently introduced by Roodsant et al as an equivalent novel organoid culture model, human fetal tissue-derived intestinal organoids were plated as a monolayer and apically inoculated with L. monocytogenes which predominantly colocalized with MUC 2-positive goblet cells [ 73 ]. Furthermore, it was noted that the fluorescent staining signal for actin became weaker in the apical region of infected cells [ 73 ].…”
Section: Bacterial Enteropathogens and Their In Vitromentioning
confidence: 99%
“…Recently introduced by Roodsant et al as an equivalent novel organoid culture model, human fetal tissue-derived intestinal organoids were plated as a monolayer and apically inoculated with L. monocytogenes which predominantly colocalized with MUC 2-positive goblet cells [ 73 ]. Furthermore, it was noted that the fluorescent staining signal for actin became weaker in the apical region of infected cells [ 73 ]. This finding might be linked to the property of L. monocytogenes to rearrange the host cell's actin into so-called “comet tails” to facilitate intracellular mobility, as previously reported by Co et al in human small intestinal organoids [ 65 ].…”
Section: Bacterial Enteropathogens and Their In Vitromentioning
confidence: 99%
“…Such an approach could lead to the discovery of new disease biomarkers and new therapeutic targets. To our knowledge, there are few publicly available reports that analyze the interaction between enteric pathogens and human isolated IECs (23,(37)(38)(39)(40)(41). More recently, Sayed et al published a study in which AIEC infection of organoid-derived 2D cultures is applied to explore host engulfment in IBD.…”
Section: Introductionmentioning
confidence: 99%